Functional symptoms in neurology: case studies. - Stone, J; Sharpe, M (2006)
In this series of case vignettes, the authors have emphasized that the diagnosis of functional symptoms should normally rest on the presence of positive evidence of the problem being functional rather than the absence of evidence of organic disease. In addition, practitioners should be prepared to make a functional diagnosis in a patient who also has evidence of disease. Misdiagnosis of functional symptoms occurs no more than for other neuro-logical and psychiatric disorders. The neurologist has an important role in being able to transmit the diagnosis in a way that will not offend the patient but will also facilitate recovery. The key elements of this explanation are making the patient feel believed and emphasizing potential reversibility. A multidisciplinary approach involving concurrent physical and psychological treatments is often recommended, although further study is required to determine the best approaches to explain and treat these conditions.